Characterization of microbial risk level of liquid waste from a private dairy factory in Bechar (Southwest Algeria) - Benyagoub, Elhassan (Indian Journal of Dairy Science, 2018)
The problem of wastewater and its purification challenges are inseparable from sustainable development in that water must meet the needs of current and future generations without mortgaging the supply capacity and their satisfaction.A challenge of waste managing worries professionals, for this is part of the present study which aims to characterize the bacteriological quality of liquid effluents from a private dairy industry in Bechar (Southwest Algeria). The analyzed bacteriological parameters target mainly contaminating microorganisms (Faecal coliforms and fecal streptococci) that are recommended by the national regulation and the international regulation of WHO, knowing that we deemed it necessary to add to these the following parameters: Enumeration of total germs, total coliforms and sulphite reducing clostridia.The analysis of a total of 10 samples revealed a high rate of faecal contamination. The average loads recorded for the various microorganisms counted were out of the ordinary, where the total and faecal coliforms had an average of log10 4.38 and log10 4.11 cfu/100mL respectively. The faecal streptococci were log10 4.38 cfu/100mL. The contamination with sulphite reducing clostridia was averaged log10 2.57 spores/100mL. However, the average load of total aerobic germs was log10 5.55 cfu/100mL.This results originally from the absence of liquid effluent treatment that are evacuated in ventilated basins, mainly three basins, each one pours the volume of wastewater towards the other basin and so on before being rejected to the sewerage network; so that, the present microorganisms progressively degrade the organic matter which it contains, but on the contrary, it will increase the microbial load.The untreated discharge of these wastewaters undoubtedly constitutes a threat to public health and to the ecosystem. The large amount of generated liquid effluents by the agri-food industry in general and from the dairy industries in particular, requires purification and recycling that can be valued in several areas namely irrigation in the agricultural sector and many others.